Death in Dallas: Sentencing patterns of pre-Furman capital offenders. Issue 2 (2nd April 2020) - El Sayed, Sarah A.; Boots, Denise Paquette; Marquart, James W.; Sanford, Stephanie M.
Abstract: Whether racial bias is intertwined with capital case dispositions continue to be a matter of contention. In 1972, Furman v. Georgia ruled capital punishment unconstitutional on the grounds of being capricious and arbitrary. To better understand this sociological phenomenon, the current paper examines capital punishment within a historical context. Specifically, the present study is an exploratory examination of county-level data consisting of offenders who received a death sentence between 1923 through 1972. Media accounts from a Dallas newspaper during that time period were also examined. Results indicate that Blacks were disproportionately sentenced to death compared to their White counterparts. Capital sentencing trends at the county level reflect national trends of racial bias that characterized this historical period.